T71. INVESTIGATING NEURAL MECHANISMS OF PROACTIVE AND REACTIVE CONTROL IN PSYCHOTIC DISORDERS WITH THE DOT PATTERN EXPECTANCY TASK. (9th April 2019) - Ma, Yizhou; Kwashie, Anita; MacDonald, Angus; Sponheim, Scott
Abstract: Background: The dot pattern expectancy (DPX) task is previously validated for cognitive control deficits in psychotic disorders. Patients with schizophrenia commit more errors as well as show less activation in bilateral prefrontal cortex during proactive control in the DPX task. Recent neural recordings in rhesus macaques indicate that proactive and reactive control processes in the DPX task engaged the same neurons in the prefrontal cortex. However, it is not clear if the overlap between these two mechanisms can be observed in human blood-oxygen-level dependent signals. Further, the role of these dual mechanism regions in the cognitive control deficits of patients with psychotic disorders remains unclear. Methods: 150 probands with a psychotic disorder, 100 first degree relatives, and 50 healthy controls in the Psychosis Human Connectome Project will complete the DPX task while undergoing 3T functional magnetic resonance imaging scan. Traditional general linear model, as well as a novel multiway method called parallel factor analysis, will be used to examine brain mechanisms involved in proactive as well as reactive control during the DPX task. Results: In a preliminary analysis of 24 probands (38.3 ± 12.8 years, 9 females) and 27 healthy controls (36.2 ± 14.0 years, 11 females), probands showed behavioral deficits in proactive control as compared to healthy controls. Neuroimaging analysis in healthy controls with general linear model showed a cluster in the left inferior frontal gyrus that was involved in both proactive and reactive control. Additionally, overlap in proactive and reactive control was observed in bilateral supramarginal/angular gyrus and right inferior occipital gyrus, although these two mechanisms also involved distinct brain regions. Discussion: Consistent with previous findings, probands showed a specific deficit in proactive control in the DPX task. Proactive and reactive control in healthy controls engaged the same brain regions in the prefrontal cortex, replicating findings in rhesus macaques. Further analyses will reveal the role of the prefrontal cortex as well as other brain regions in the cognitive control deficits in psychotic disorders.